2019
DOI: 10.1007/s10943-019-00786-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Compassion Levels of Nurses Working at a University Hospital

Abstract: This study was conducted to determine the compassion levels of nurses working in a university hospital. The study sample consists of 227 nurses who were available and participated in the research voluntarily during the study. The study data were collected by using "Nurse Description Form" and "Compassion Scale (CS)." In the analysis of the study data, number, percentage, mean and independent T test and ANOVA test were used. The total mean score of CS of the nurses was found as 97.02 ± 10.67. There was no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 14 publications
5
30
3
4
Order By: Relevance
“…Mealer and colleagues found that intensive care unit (ICU) nurses caring for highly complex critical patients had higher levels of traumatic stress than medical and surgical nurses (Mealer et al 2007 ). Whereas in another study, a significant difference was determined between the working clinic and compassion fatigue level (Arkan et al 2020 ). The literature review reports that nurses working in intensive care, emergency, oncology and surgical clinics experience greater compassion fatigue (Potter et al 2010 ; Sacco et al 2015 ; Jenkins and Warren 2012 ; Denk 2018 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mealer and colleagues found that intensive care unit (ICU) nurses caring for highly complex critical patients had higher levels of traumatic stress than medical and surgical nurses (Mealer et al 2007 ). Whereas in another study, a significant difference was determined between the working clinic and compassion fatigue level (Arkan et al 2020 ). The literature review reports that nurses working in intensive care, emergency, oncology and surgical clinics experience greater compassion fatigue (Potter et al 2010 ; Sacco et al 2015 ; Jenkins and Warren 2012 ; Denk 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…Our study identified that nurses scored 14.3 ± 7.7 on the compassion fatigue scale and experienced low levels of compassion fatigue, while Kim's research found that nurses experience moderate levels of compassion fatigue (Kim 2013 ). The results of the research in Turkey showed that the nurses had moderate levels of compassion fatigue (Yeşil et al 2010 ; Kara and Çitak 2018 ; Hür and Ekinci 2018 ; Arkan et al 2020 ). There was a positive correlation between nurses' work-related stress and compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies have reported similar results to the present study (Arlı et al 2018;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Büyük et al 2021;Karadağ et al 2018). In the study by Arkan (2020), nurses had a medium compassion level (Arkan et al 2020). Compassion is the feeling that arises in witnessing another's suffering and that motivates a subsequent desire to help (Goetz et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…10 A quality nursery care for patients and increasing the quality of their lives is only possible with a compassionate approach to the patients. 8 The level of compassion of the nurses has an important part in good care.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nurses can provide quality and professional service for patients by approaching them with the sense of compassion during care. 8 During the treatment and patient care, the health professionals who spend the most time with patients are nurses and they are the first person patients/patient relatives consult in the case of a problem. Therefore, compassion the nurses'…”
Section: Araştırma Makalesimentioning
confidence: 99%